Population structure and weight-length relationship of Hyphessobrycon bifasciatus Ellis 1911 in a dammed stream - Thiago Mündel Ribeiro Santos; Julia Fernanda de Camargo Teles Miranda; Talita Rolim de Freitas Lima; Flavia Conceição de Paiva; Natalia Silva Alves; Welber Senteio Smith (Acta Scientiarum. Biological Sciences, 2024)
The species gacor slot Hyphessobrycon bifasciatus, also known as the 'lemon tetra', is a small characin fish distributed in coastal rivers from the southern state of Bahia to the state of Rio Grande do Sul, and also in the upper Paraná river basin, found in small rivers and lagoons. Its diet varies between small invertebrates and plant debris. They are oviparous animals that lay their eggs on the bottom or in groups of plants, which hatch approximately two days after fertilization. In light of this, the present study aimed to describe the population structure of H. bifasciatus in terms of feeding and length-weight relationship in a dammed neotropical stream located in the municipality of São Roque, SP, Brazil. Specimens of H. bifasciatus were captured in two collection campaigns (November 2021 and July 2022). The fish were collected using a three-meter-long trawl net, with a 1 cm mesh and a sampling effort of 30 minutes at each point. Subsequently, they were transported to the laboratory, where their length and standard weight were recorded, along with their stomach contents. A total of 101 specimens were analyzed, 41 females and 60 males. The species had an average body length of 2.5 ± 0.46 cm and an average total weight of 0.33 ± 0.19 g for females, and 2.8 ± 0.60 cm and 0.45 ± 0.27 g for males. We obtained a length-weight relationship of y = 0.4317x - 0.7574, R² = 0.9393 for males, and y = 0.3413x - 0.5237, R² = 0.8704 for females. The size range varies from the 1.6-2.0 centimeter class to the 3.6-4.0 centimeter class. The main food items were plant material and filamentous gacor slot algae, abundant in both sexes. Finally, it is concluded that this species forms large schools near macrophytes, exhibits peaceful behavior, and feeds mainly on plant items.